Can reed harvest be used as a management strategy for improving invertebrate biomass and diversity? - Andersen, Line Holm; Nummi, Petri; Rafn, Jeppe; Frederiksen, Cecilie Majgaard Skak; Kristjansen, Mads Prengel; Lauridsen, Torben Linding; Trøjelsgaard, Kristian; Pertoldi, Cino; Bruhn, Dan; Bahrndorff, Simon (Journal of environmental management, 2021)
The succession-driven reed bed habitat hosts a unique flora and fauna including several endangered invertebrate species. Reed beds can be managed through commercial winter harvest, with implications for reed bed conservation. However, the effects of winter harvest on the invertebrate community are not well understood and vary across studies and taxonomic levels. The aim of this study was to investigate the effects of reed harvest on invertebrate communities. Ground-dwelling and aerial invertebrates were continuously sampled for 10 weeks in the largest coherent reed bed of Scandinavia in order to assess how time since last reed harvest (0, 3, and 25-years) influences invertebrate biomass, biodiversity and community structure across taxonomic levels. Biomass was measured and all specimens were sorted to order level, and Coleoptera was even sorted to species level. The invertebrate community showed distinct compositional differences across the three reed bed ages. Furthermore, biomass of both aerial and ground-dwelling invertebrates was highest in the age-0 reed bed and lowest in the age-25 reed bed. Generally, biodiversity showed an opposite trend with the highest richness and diversity in the age-25 reed bed. We conclude that it is possible to ensure high insect biomass and diversity by creating a mosaic of reed bed of different ages through small-scale harvest in the largest coherent reed bed in Scandinavia. The youngest red beds support a high invertebrate biomass whereas the oldest reed beds support a high biodiversity. Collectively, this elevate our understanding of reed harvest and the effects it has on the invertebrate communities, and might aid in future reed bed management and restoration. [Display omitted] •Reed bed age impacted the invertebrate community composition.•Invertebrate biomass was highest in the recently managed reed bed.•Invertebrate diversity was highest in the long-term unmanaged reed bed.•Correct management can simultaneously ensure high biomass and high diversity.